PEMBERDAYAAN FUNGSI MASJID RAYA DARUSSALAM PALANGKARYA - Asmawati, Asmawati (LP2M IAIN Palangka Raya, 2013)
The problems of the study were: 1) the role of Darussalam Mosque in Palangka Raya, 2) the problems in maximizing the role of Darussalam Mosque in Palangka Raya, and 3) the implementation solutions of the role of Darussalam Mosque in Palangka Raya.The study used descriptive qualitative. The methods applied in the study covered: a) participatory observation, b) in-depth interview, and c) documentation. The data analysis applied in the study covered: a) data collection, b) data reduction, c) data display, and d) drawing conclusion and verification.Â The results of the study could be described as follows: 1) the Palangka Raya Darussalam Mosque was functioned for education and daâwa. This could be seen from education activities and daâwa such as the 7-minute Islamic preaching during the Ramadhan, Islamic teaching for Muslim female, kindergarten and Qurâanic education school (TK-TPA), the Islamic preaching for Friday prayers and Holy days (the Fitri and Adha days), and the celebration of Islamic Great Days (PHBI). 2) As for social functions, it could be seen in wedding ceremony, witnessing to embrace Islam for new Muslim followers (muallaf), meeting for mosque board members, accepting the visiting of guests both from the government officers and Islamic mass organization, giving aids for the poor through iftar activity, distributing the zakat in the Fitri days, and distributing meat at the Adha days. 3) The mosque was also functioned as art and culture covering the Maulid Habsyi activity, MTQ (Qurâanic Reciting Competition), the Anak Saleh festivals, religious competitions, boy scouting for TK-TPA students around Palangka Raya.Â Â